2010
DOI: 10.1248/bpb.33.40
|View full text |Cite
|
Sign up to set email alerts
|

Matrine Induces Cell Anergy in Human Jurkat T Cells through Modulation of Mitogen-Activated Protein Kinases and Nuclear Factor of Activated T-Cells Signaling with Concomitant Up-Regulation of Anergy-Associated Genes Expression

Abstract: T cell activation plays a pivotal role in the pathogenesis of human autoimmune and chronic inflammatory illnesses. In the past decades, great efforts have been made to find immunosuppressants that can intervene in T cell activation and proliferation. However, in treatment of some refractory cases of these illnesses, immunosuppressants must be taken for long-term, even life-long, in spite of various side effects. Therefore, T cell immunotolerance induction leading to T cells anergy has been becoming a promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
(29 reference statements)
2
20
0
Order By: Relevance
“…Although anergy has been associated with decreased activation of TCR-associated kinases, such as Akt, PI3K, PKC, and MAPK (ERK-1/2) (43)(44)(45), other studies have demonstrated either no differences or increased activation levels of these kinases in anergic cells (29,34,46). The current evidence supports a model in which the main hallmark of the anergic state is a block in G1-to-S progression during the cell cycle (34,47,48).…”
Section: Discussionsupporting
confidence: 70%
“…Although anergy has been associated with decreased activation of TCR-associated kinases, such as Akt, PI3K, PKC, and MAPK (ERK-1/2) (43)(44)(45), other studies have demonstrated either no differences or increased activation levels of these kinases in anergic cells (29,34,46). The current evidence supports a model in which the main hallmark of the anergic state is a block in G1-to-S progression during the cell cycle (34,47,48).…”
Section: Discussionsupporting
confidence: 70%
“…The herb's clinical effects were believed to be dependent on its active molecule, C 15 H 24 N 2 O, an alkaloid also known as matrine ( Figure 1). Matrine has many biological activities and exerts many biological effects, such as anti-inflammation, anti-fibrosis, and immune regulation [10][11][12] . Although they are rarely mentioned, the anti-oxidant properties of matrine have been described in www.nature.com/aps Liu ZW et al Acta Pharmacologica Sinica npg previous studies [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Matrine, an alkaloid extracted from Sophora flavescens Aif, is quinolizidine with four-loop and molecular formula of C 15 H 24 N 20 . Matrine has been found to exhibit many biological activities, such as anti-inflammation, anti-virus, anti-fibrosis, anti-arrhythmia, and immunosuppression, leading to wide clinical use in the treatment of viral hepatitis, liver fibrosis, heart arrhythmia and skin diseases in China [6][11]. Recently, intensive studies have shown that matrine possesses potent antitumor activities by inhibiting proliferation and inducing apoptosis of cells from gastric cancer, lung cancer, hepatocellular carcinoma, breast cancer, melanoma, leukemia, multiple myeloma [12][21].…”
Section: Introductionmentioning
confidence: 99%